Non-Performing Loan in Nepalese Commercial Banks: The Role of Internal and External Factors - Hamal, Janga Bahadur; Sharma, Dilli Raj; Budhathoki, Prem Bahadur; Jha, Navin; Ghimire, Shiva Raj (Nepal Journal of Multidisciplinary Research, 2025)
Background: Non-performing loan is one of the key indicators for regulators in assessing the bank's financial stability and asset quality, as it refers to the loan where principal or interest payments are overdue by 90 days or more, or when there is uncertainty regarding full repayment. This paper aims to examine the effect of internal and external factors on non-performing loan of Nepalese commercial banks. Methods: The study employed explanatory research design using 280 quarterly observations for twenty Nepalese commercial banks for the period from the first quarter of 2021 to second quarter of 2024. The econometric models used to analyze the balanced panel data are fixed effect and random effect model. Results: The results depict that capital adequacy and credit to deposit ratio have negative significant impact on the NPL, whereas liquidity and prescribed sector’s lending have positive significant impact on the NPL. The rate of lending interest has insignificant impact on NPL. Similarly, inflation and GDP growth rate have positive significant impact on NPL of Nepalese commercial banks during the observed period. Conclusion: The study concludes that the internal factors such as capital adequacy ratio and credit-to-deposit ratio, along with the external factor of GDP growth, significantly influence non-performing loan ratios in Nepalese commercial banks. The study also highlights the need for robust capital management, enhanced credit monitoring, and stable macroeconomic policies to mitigate default risks and improve asset quality within the sector. Novelty: The literature offers consistent findings for some other studies in the area while a broader analysis is lacking for other banking and financial institutions in the Nepalese context. The present study considers all the commercial banks with quarterly data, and supports the idea that a higher financial performance is correlated to lower level of NPL. Hence, policy makers are advised to monitor internal bank specific and external macroeconomic indicators to reduce NPL.